Influência da tipologia do contraventamento em sistemas estruturais light steel frame - Silva, Syndel Flavia Lopes da (2022)
The Light Steel Frame System has been used on a large scale in countries where civil construction has progressed at significant levels of industrialization, this constructive method of rational design has as main characteristics the speed of execution and greater lightness of the structural components. In Brazil, the LSF system is still not widely used, due to cultural barriers and the lack of civil construction professionals who are really prepared to work with the system. In search of demystifying that the LSF is a fragile system, this work aimed to evaluate the influence of different types of bracing, modulated in the Light Steel Framing system, in order to guarantee the structural stability of a shed executed with heavy profiles in steel. For this, a pre-dimensioned structural project in heavy profiles was adapted by replacing the original bracing with LSF panels, in which nine different bracing typologies were elaborated. With the help of the MCalcLSF software, the structure was discretized into bar and nodes to be evaluated for the influence of bracing. In the end, results were obtained that showed that the tape bracing with an “X” arrangement was the one that provided the smallest horizontal displacements, followed by the modulation of the simple diagonal type.